2006
DOI: 10.1016/j.ccr.2006.05.023
|View full text |Cite
|
Sign up to set email alerts
|

HER2 kinase domain mutation results in constitutive phosphorylation and activation of HER2 and EGFR and resistance to EGFR tyrosine kinase inhibitors

Abstract: HER2/Neu gene mutations have been identified in lung cancer. Expression of a HER2 mutant containing a G776(YVMA) insertion in exon 20 was more potent than wild-type HER2 in associating with and activating signal transducers, phosphorylating EGFR, and inducing survival, invasiveness, and tumorigenicity. HER2(YVMA) transphosphorylated kinase-dead EGFR(K721R) and EGFR(WT) in the presence of EGFR tyrosine kinase inhibitors (TKIs). Knockdown of mutant HER2 in H1781 lung cancer cells increased apoptosis and restored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
349
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 418 publications
(361 citation statements)
references
References 48 publications
12
349
0
Order By: Relevance
“…It induced transphosphorylation of kinase‐dead EGFR, and exhibited higher ligand‐independent tyrosine phosphorylation. Moreover, the insertions were more potent than wide‐type HER‐2 in associating with signal transducers that mediate proliferative and prosurvival responses 44.The activating missense mutations in kinase domain have also been reported. Most of the mutations were detected in the αC‐helix which is considered to play a critical role in the activation of HER‐2 gene 23.…”
Section: The Her‐2 Mutations and Variantsmentioning
confidence: 98%
See 2 more Smart Citations
“…It induced transphosphorylation of kinase‐dead EGFR, and exhibited higher ligand‐independent tyrosine phosphorylation. Moreover, the insertions were more potent than wide‐type HER‐2 in associating with signal transducers that mediate proliferative and prosurvival responses 44.The activating missense mutations in kinase domain have also been reported. Most of the mutations were detected in the αC‐helix which is considered to play a critical role in the activation of HER‐2 gene 23.…”
Section: The Her‐2 Mutations and Variantsmentioning
confidence: 98%
“…These insertions are more potent in transphosphorylating EGFR compared with the wild‐type HER‐2. Conclusively, the mutant HER‐2 gene is more transforming and more capable to inhibit the effect of apoptosis 44.…”
Section: The Her‐2 Mutations and Variantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies [51] have shown cells harboring HER2 mutations undergoing constitutive phosphorylation and activation of HER2 and show resistance to EGFR TKIs. Treatment with small-molecule tyrosine kinase inhibitors that target the kinase activity of both EGFR and HER2 eg Lapatinib, tested as HKI-272, have been found to be effective.…”
Section: Her2 As a Therapeutic Targetmentioning
confidence: 95%
“…They are reported in 2% of NSCLC [50,51]. ERBB2/HER2 mutations involve inframe insertions in exon 20, mostly involving the amino acid sequence Tyr-Val-Met-Ala at codon 776.…”
Section: Erbb2 (Her2)mentioning
confidence: 99%